Methane cold seeps as biological oases in the high‐Arctic deep sea. (27th October 2017) - Åström, Emmelie K. L.; Carroll, Michael L.; Ambrose, William G.; Sen, Arunima; Silyakova, Anna; Carroll, JoLynn
Abstract: Cold seeps can support unique faunal communities via chemosynthetic interactions fueled by seabed emissions of hydrocarbons. Additionally, cold seeps can enhance habitat complexity at the deep seafloor through the accretion of methane derived authigenic carbonates (MDAC). We examined infaunal and megafaunal community structure at high‐Arctic cold seeps through analyses of benthic samples and seafloor photographs from pockmarks exhibiting highly elevated methane concentrations in sediments and the water column at Vestnesa Ridge (VR), Svalbard (79° N). Infaunal biomass and abundance were five times higher, species richness was 2.5 times higher and diversity was 1.5 times higher at methane‐rich Vestnesa compared to a nearby control region. Seabed photos reveal different faunal associations inside, at the edge, and outside Vestnesa pockmarks. Brittle stars were the most common megafauna occurring on the soft bottom plains outside pockmarks. Microbial mats, chemosymbiotic siboglinid worms, and carbonate outcrops were prominent features inside the pockmarks, and high trophic‐level predators aggregated around these features. Our faunal data, visual observations, and measurements of sediment characteristics indicate that methane is a key environmental driver of the biological system at VR. We suggest that chemoautotrophic production enhances infaunal diversity, abundance, and biomass at the seep while MDAC create a heterogeneous deep‐sea habitat leading to aggregation of heterotrophic, conventional megafauna. Through this combination of rich infaunal and megafaunal associations, the cold seeps of VR are benthic oases compared to the surrounding high‐Arctic deep sea.